Standard Operating Procedure for Personal Hygiene in the Kitchen of the Grand Rohan Hotek Yogyakarta - Lutfi Hendriyati; Ardi Surwiyanta, Ardi Surwiyanta; Melia Dwi Sukmawati , Melia Dwi Sukmawati (Journal of Tourism and Creativity, 2025)
The implementation of good personal hygiene will affect the image and reputation of the hotel. Therefore, hotels are expected to implement high standards of cleanliness, including aspects of employee personal hygiene, as a form of commitment to excellent service, comfort and safety for guests. The formulation in this study is: How is the Standard Operating Procedure for Personal Hygiene in the Kitchen of the Grand Rohan Hotel Yogyakarta. and What are the Constraints of the Standard Operating Procedure for Personal Hygiene in the Kitchen of the Grand Rohan Hotel Yogyakarta.